Adam Gopnik, The Table Comes First. Family, France, and the Meaning of Food - Hayward, Vicky (Petits Propos Culinaires, 2013)
Adam Gopnik, The Table Comes First. Family, France, and the Meaning of Food, Quercus, 2011, 293pp, hardback: ?18.99 (paperback: £11.04).